1975
DOI: 10.1172/jci108220
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of apoprotein B of plasma very low density lipoproteins in the rat.

Abstract: A B S T R A C T As an extension

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(38 citation statements)
references
References 26 publications
(25 reference statements)
5
33
0
Order By: Relevance
“…Previous studies ( 16) demonstrating the poor conversion of VLDL to LDL in rats are confirmed by these observations. The a or high density lipoproteins appear ( 17) to have a primary role in the net return of cholesterol from peripheral tissues to the liver.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies ( 16) demonstrating the poor conversion of VLDL to LDL in rats are confirmed by these observations. The a or high density lipoproteins appear ( 17) to have a primary role in the net return of cholesterol from peripheral tissues to the liver.…”
Section: Discussionsupporting
confidence: 81%
“…This possibility has been invoked by other workers (50,51) including a preliminary report using the same methodology as employed in this work (52). Second, the "remnant" of VLDL may be removed by pathways other than conversion to LDL, particularly in hyperlipidemic subjects, as suggested for man by the work of Sigurdssoni et al (49), Reardlon et al (15), and Bermlani et al (53), anid for rats by Faergeman et al (54).…”
Section: Discussionmentioning
confidence: 97%
“…While (39,40), and it has also been shown that more than half of LDL particles are taken up by liver in rabbits (20); thus the transfer pathway would be expected to deliver HDL cholesterol esters mostly to the liver. In the case of selective uptake, the pathway occurs predominantly (-90%) in the liver in rats (10).…”
Section: Discussionmentioning
confidence: 99%